GAMBARAN MOTIVASI BERMAIN PARA PEMAIN MMORPG YANG TERGOLONG HIGH ENGAGEMENT GAMER - Vivekananda Lengkong; Ignatius Darma Juwono (MANASA, 2013)
Innovation and development of technology has created situation at which agamer plays online with different individuals around the world at the same time.With beautiful visual design and interesting gameplay, a player could spend hours excessively playing games. This, in turn, can create problems as the player has many obligations in their routine. This article focuses on what causing a gamer willing to spend hours playing online games. The concept of motivation underlies this research. This research intends to investigate factors that drive a gamer to play excessively. Motivation can be defined as internal and intrapsychic processes within individual which drive him toward certain direction. In gaming world, three factors are known to drive a person plays games excessively: achievement, social, and immersion. Two excessive Massively Multiplayer Online Role Playing Game (MMORPG) players are interviewed to get information regarding their playing behaviors as well as the underlying motives of playing. Result shows that both participants used MMORPG as refreshing activities from their daily routine. While both see MMORPG as fun, they differ in their drive to achieve and socialize while playing games. Further analysis and impact of the finding is then discussed.